Branched PBAT resin and preparation method thereof, foam material and preparation method thereof

By introducing rigid and flexible branching points into PBAT resin to form a dynamic crosslinking network, the balance problem between foaming and degradation properties of PBAT materials is solved, the foaming ratio and degradation properties are improved, and the combination of high resilience and degradability is achieved.

CN120365542APending Publication Date: 2025-07-25SHANGHAI HUAFON NEW MATERIAL R&D TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510682019.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

Existing PBAT materials are difficult to balance between foaming performance and degradation performance, especially in terms of foaming ratio and resilience, which leads to limited application in the field of foaming materials.

Method used

By introducing rigid branching points and flexible branching points into PBAT resin, the proportion in the resin is controlled, and a dynamic crosslinking network with "hardness and flexibility" is formed, which enhances the mechanical strength and toughness of the bubble wall, and improves the foaming ratio and degradation performance.

Benefits of technology

The PBAT material has achieved excellent degradation performance while improving the foaming ratio. The cell has both stability and reversible deformation capabilities, which significantly improves the dynamic rebound performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120365542A_ABST
    Figure CN120365542A_ABST
Patent Text Reader

Abstract

The invention discloses branched PBAT resin and a preparation method thereof, and a foam material and a preparation method thereof, and relates to the technical field of foam materials. According to the invention, rigid branching points and flexible branching points are introduced into the branched PBAT resin, and the introduction amount is controlled, so that the material has excellent foaming performance and degradation performance at the same time. Specifically, the rigid branching points can enhance the mechanical strength of the bubble wall, prevent the bubbles from collapsing or merging, effectively resist external force deformation and maintain the stability of the bubble structure; the flexible branching points can improve the toughness of the bubble wall, so that the bubbles can be elastically deformed instead of being broken when being pressed, the mobility of molecular chains is increased, and the material is easier to restore deformation after being stressed. The rigid part and the flexible part are combined to form a rigid-flexible dynamic cross-linked network; the rigid part provides support and limits excessive deformation; the flexible part endows elasticity, and deformation recovery is promoted. The balanced network enables the cells to have both stability and reversible deformation ability, and the dynamic resilience is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of foaming materials, and in particular, to a branched PBAT resin, a preparation method thereof, a foam material, and a preparation method thereof. Background Art

[0002] Non-degradable materials such as polyethylene, polystyrene, and polyurethane have long dominated the foaming material market. These materials are widely used in various fields, including packaging, construction, agriculture, and daily necessities. However, these materials are difficult to degrade naturally after being discarded, thus causing serious environmental pollution. Especially in the marine and farmland environments, the problem of microplastic pollution caused by disposable foamed products is particularly prominent. Currently, the proportion of disposable foamed products in the total plastic waste is still relatively high, and it is imperative to develop biodegradable materials, such as the high-production-capacity biodegradable material poly(butylene adipate-co-terephthalate) (PBAT). However, PBAT still has significant defects in foaming performance, which greatly limits its wide application in the field of foaming materials.

[0003] Insufficient melt strength is one of the main factors restricting the foaming performance of degradable materials. Due to the linear molecular chain structure of PBAT, the foaming ratio of PBAT during the foaming process is generally low, usually less than 20 times, resulting in insufficient resilience of the material. In order to improve the resilience of the material, crosslinking modification and blending modification methods are usually used, but these methods often have insufficient resilience modification and even seriously sacrifice the degradation performance of the material. It is difficult to balance the resilience and degradation performance of PBAT materials, and the existing improvement methods cannot fully balance the foaming performance and degradation performance of the material.

[0004] Therefore, there is an urgent need to improve PBAT materials so that they can meet the requirements of degradability while increasing the foaming ratio.

[0005] In view of this, the present invention is specifically proposed. Summary of the Invention

[0006] The purpose of the present invention is to provide a branched PBAT resin, a preparation method thereof, a foam material, and a preparation method thereof, aiming to meet the requirements of degradability while increasing the foaming ratio.

[0007] The present invention is implemented as follows:

[0008] In the first aspect, the present invention provides a branched PBAT resin, which includes PBAT chain segment units and branching points;

[0009] The branching points include rigid branching points and flexible branching points, and the total mass ratio of the reaction raw materials of the rigid branching points and the flexible branching points to the mass of the reaction product of the branched PBAT resin is at most 0.4:100;

[0010] Among them, the rigid branching points are formed by carboxylic acid compounds containing rigid groups entering the molecular chain through an esterification reaction, and the structure of the carboxylic acid compounds containing rigid groups contains three or more carboxyl groups;

[0011] The flexible branching points are formed by hydroxyl compounds containing flexible groups entering the molecular chain after an esterification reaction, and the structure of the hydroxyl compounds containing flexible groups contains three or more hydroxyl groups;

[0012] The branched PBAT resin also includes non-PBAT segment units, and the mass ratio of the total reaction raw materials constituting the non-PBAT segment units to the mass of the reaction product of the branched PBAT resin is (0 - 5):100.

[0013] In an alternative embodiment, the mass ratio of the total reaction raw materials of the rigid branching points and the flexible branching points to the mass of the reaction product of the branched PBAT resin is at least 0.2:100;

[0014] And / or, in the total reaction raw materials of the rigid branching points and the flexible branching points, the mass ratio of the reaction raw materials of the rigid branching points is 30% - 70%;

[0015] And / or, the carboxylic acid compounds containing rigid groups forming the rigid branching points are selected from at least one of trimesic acid, pyromellitic acid, trimellitic acid, and naphthalenetetracarboxylic acid;

[0016] And / or, the hydroxyl compounds containing flexible groups forming the flexible branching points are aliphatic polyols; preferably, the hydroxyl compounds containing flexible groups are selected from at least one of glycerol, pentaerythritol, xylitol, and sorbitol.

[0017] In an alternative embodiment, the non-PBAT segment unit is a flexible segment; preferably, the flexible segment is a polyether segment, and the polyether segment is copolymerized into the PBAT segment by means of an ester bond; more preferably, the polyether segment is selected from at least one of a polyethylene glycol segment, a polytetrahydrofuran segment, a polytrimethylene ether glycol segment, and a polypropylene glycol segment;

[0018] The mass ratio of the total reaction raw materials of the flexible segment to the mass of the reaction product of the branched PBAT resin is (3 - 5):100.

[0019] In an alternative embodiment, the polyether segment is a polytetrahydrofuran segment;

[0020] Preferably, the polytetrahydrofuran segment is composed of a high molecular weight polytetrahydrofuran segment and a low molecular weight polytetrahydrofuran segment; the number average molecular weight of the high molecular weight polytetrahydrofuran segment is 1800 - 3000, and the number average molecular weight of the low molecular weight polytetrahydrofuran segment is 250 - 1000; the difference in the number average molecular weight between the high molecular weight polytetrahydrofuran segment and the low molecular weight polytetrahydrofuran segment is greater than or equal to 600;

[0021] More preferably, the mass ratio of the reaction raw materials constituting the high molecular weight polytetrahydrofuran segment in the total amount of the reaction raw materials constituting the polytetrahydrofuran segment is 20% - 80%.

[0022] In an alternative embodiment, in the PBAT segment, the molar ratio of adipic acid units to terephthalic acid units is (51 - 55):(45 - 49);

[0023] and / or, the terminal hydroxyl group content of the branched PBAT resin is less than or equal to 15 mol / t;

[0024] and / or, the number average molecular weight of the branched PBAT resin is greater than 80000 g / mol.

[0025] In a second aspect, the present invention provides a method for preparing the branched PBAT resin according to any one of the foregoing embodiments, comprising: using adipic acid, terephthalic acid, 1,4 - butanediol, a chain extender, and a branching agent as main raw materials to prepare the branched PBAT resin;

[0026] wherein, the branching agent includes a carboxylic acid compound containing a rigid group and a hydroxyl compound containing a flexible group.

[0027] In an alternative embodiment, it includes esterification, polycondensation, and chain extension in sequence; among them, the esterification is carried out by the transesterification method or the direct esterification method;

[0028] Preferably, the preparation process includes:

[0029] Parallel esterification: Mix and react adipic acid, 1,4 - butanediol, and a hydroxyl compound containing a flexible group to obtain a first esterification product; mix and react terephthalic acid, 1,4 - butanediol, a carboxylic acid compound containing a rigid group, a non - PBAT segment compound, and an esterification catalyst to obtain a second esterification product;

[0030] Mixed transesterification: Mix and react the first esterification product and the second esterification product to obtain an esterification intermediate;

[0031] Polycondensation: Carry out polycondensation on the esterification intermediate to make the number average molecular weight reach 16000 - 25000 to obtain a polycondensation thickening product;

[0032] Chain extension: The polycondensation thickening product is mixed and reacted with a chain extender to obtain a polymer with a terminal carboxyl content of less than 15 mol / t and a number average molecular weight of greater than 80,000 g / mol.

[0033] In an alternative embodiment, during the preparation of the first esterification product, the molar ratio of adipic acid to 1,4-butanediol is controlled to be 1:(1.1 - 1.4), and the esterification rate is controlled to be greater than 90%;

[0034] Preferably, during the preparation of the second esterification product, the molar ratio of terephthalic acid to 1,4-butanediol is controlled to be 1:(1.6 - 2.2), and the esterification rate is controlled to be greater than 95%.

[0035] Thirdly, the present invention provides a method for preparing a foam material, which is prepared by using any one of the branched PBAT resins in the foregoing embodiments or any one of the branched PBAT resins in the foregoing embodiments;

[0036] Preferably, the preparation process includes: subjecting the branched PBAT resin to high-pressure impregnation with a supercritical gas, and then releasing the pressure;

[0037] More preferably, the supercritical gas is supercritical carbon dioxide;

[0038] More preferably, the operating pressure of the high-pressure impregnation is 15 MPa - 25 MPa, the temperature is 100 °C - 120 °C, and the impregnation time is 2 h - 4 h;

[0039] More preferably, the pressure release rate is 5 MPa / s - 10 MPa / s.

[0040] Fourthly, the present invention provides a foam material, which is prepared by using the preparation method of the foregoing embodiment;

[0041] Preferably, the foaming ratio of the foam material is 20 - 25 times, the falling ball rebound rate ≥ 75%, and the degradation rate after 180 days > 90%.

[0042] The present invention has the following beneficial effects: within a certain range, the foaming ratio increases with the increase of the branching point content, and thus the resilience is also improved, but the degradation performance of the material decreases with the increase of the branching point content. Therefore, generally, too many branching points cannot be introduced. The present invention introduces rigid branching points and flexible branching points into the branched PBAT resin and controls the introduction amount, enabling the material to simultaneously possess excellent foaming performance and degradation performance. Specifically, the rigid branching points can enhance the mechanical strength of the cell wall, prevent cell collapse or coalescence, effectively resist external force deformation, and maintain the stability of the cell structure; the flexible branching points can improve the toughness of the cell wall, enable the cells to elastically deform rather than rupture when compressed, increase the mobility of molecular chains, and make the material more easily recover deformation after being stressed. The combination of the two forms a "rigid-flexible combined" dynamic cross-linked network: the rigid part provides support and limits excessive deformation; the flexible part endows elasticity and promotes deformation recovery. This balanced network enables the cells to have both stability and reversible deformation ability, significantly improving the dynamic resilience performance. Brief Description of the Drawings

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other related drawings can also be obtained based on these drawings.

[0044] Figure 1 It is a schematic structural diagram of the branched PBAT resin provided by the embodiment of the present invention. Detailed Embodiments

[0045] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. For those conditions not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.

[0046] It should be understood that the direct esterification method and the transesterification method for preparing PBAT are two conventional and well-known mature polyester production technologies. The selective disclosure of the direct esterification method for preparing PBAT in this application does not constitute a special limitation on the present invention. Those skilled in the art can also choose the transesterification method to obtain the corresponding branched PBAT resin.

[0047] It should be understood that in the process of preparing PBAT by the direct esterification method, the well-known A esterification process does not require a catalyst. After introducing a flexible branching agent, the reaction can still be autocatalyzed without a catalyst. The reaction conditions of A esterification are controlled to make the esterification rate greater than 90%, ensuring the smooth progress of subsequent reactions. The control of the esterification rate is a conventional technique for the PBAT esterification reaction. Exemplarily, the reaction temperature can be controlled at 180°C - 210°C, the reaction pressure is maintained at 60 - 100 kPa(A), and the reaction time is 2h - 4h.

[0048] It should be understood that in the process of preparing PBAT by the direct esterification method, the well-known T esterification process generally uses an esterification catalyst. The selected T esterification catalyst is a conventional catalyst for PBAT. When introducing a rigid branching agent and a flexible polymer segment, the reaction promoted by its active sites is still an esterification reaction. The conventional PBAT is still applicable to the catalysis of the new system. The examples only show one type of catalyst and do not constitute a special limitation to the present invention. Those skilled in the art can also select other commonly used catalyst types and addition amounts, which belong to conventional polymerization adjustments, for the catalytic polymerization process and will not be further discussed in the examples. Exemplarily, the T esterification catalyst in the examples can be a catalyst prepared by compounding tetra-isopropyl titanate and trioctyl phosphate at a Ti / P molar ratio of 10 / 1, and the catalyst addition amount is 600 - 1000 ppm. Exemplarily, the control of the esterification rate of T esterification is a conventional technique for the PBAT esterification reaction. Exemplarily, the reaction temperature can be controlled at 230°C - 250°C, the reaction pressure is maintained at 40 - 80 kPa(A), and the reaction time is 2h - 4h. In the examples and comparative examples of the present invention, the T esterification catalyst used is a catalyst prepared by compounding tetra-isopropyl titanate and trioctyl phosphate at a Ti / P molar ratio of 10 / 1, and the addition amount of the catalyst is 800 ppm.

[0049] It should be understood that mixed transesterification is to mix the products of A esterification and T esterification, so that the two esterification products are fully transesterified to form a uniform intermediate. The molar ratio of AA to PTA is 51 / 49 to 55 / 45, and the reaction conditions are controlled to ensure that the esterification rate of the reactants exceeds 98.5%. Exemplarily, the reaction temperature is controlled at 220°C - 240°C, the reaction pressure is maintained at 60 - 80 kPa(A), and the reaction time is 1h - 3h. In this stage, by precisely controlling the esterification rate reaction conditions, the two esterification products are fully transesterified to form a uniform intermediate.

[0050] It should be understood that the types and addition amounts of catalysts used in the polycondensation process belong to the conventional adjustments of the existing PBAT polymerization technology and are used to catalyze the polymerization process, which will not be discussed in detail in the examples. Exemplarily, the polycondensation catalyst can be a compound product of titanate and phosphate ester, and the Ti / P molar ratio in the catalyst is 10 / 1 to 10 / 3, such as 10:1, 10:2, 10:3, etc. The titanate can be any one of tetra-n-butyl titanate, tetra-isopropyl titanate, triisostearoyl titanate isopropyl ester, and isopropyl dioleoyl (dioctylphosphate acyloxy) titanate, and the titanate can be any one or several of the above. The phosphate ester is any one of triphenyl phosphate, trioctyl phosphate, tris(2-ethylhexyl) phosphate, and lauryl phosphate, and the phosphate ester can be any one or several of the above. Exemplarily, in the examples, the polycondensation catalyst is (a compound of tetra-isopropyl titanate and trioctyl phosphate with a Ti / P molar ratio of 10 / 3), the catalyst addition amount is 300-500 ppm, and the number-average molecular weight after polycondensation is controlled to reach 16,000-25,000. The specific process of polycondensation is not limited. For example, pre-polycondensation can be carried out first to make the degree of polymerization of the reactants reach 20-30, and then final polycondensation is carried out to further increase the degree of polymerization of the reactants to 80-120. In the pre-polycondensation process, 300 ppm-500 ppm of the polycondensation catalyst based on the mass of the theoretical final product is added to the mixed transesterification product, the reaction temperature is controlled at 220°C-240°C, the reaction pressure is maintained at 1-3 kPa(A), and the reaction time is 2 h-3 h. In the final polycondensation process: the reaction temperature is controlled at 225°C-235°C, the reaction pressure is maintained below 150 Pa(A), and the reaction time is 3 h-4 h. In the examples and comparative examples of the present invention, the polycondensation catalyst used is a compound formed by tetra-isopropyl titanate and trioctyl phosphate with a Ti / P molar ratio of 10 / 3, the catalyst addition amount is 400 ppm, and the polycondensation is carried out in one step without being divided into two steps of pre-polycondensation and final polycondensation.

[0051] It should be understood that the type of chain extender used in the chain extension process can be selected within a wide range. The types of conventional PBAT chain extenders such as hexamethylene diisocyanate and 4,4'-diisocyanate dicyclohexylmethane are not discussed in detail in the examples. The chain extenders used in the following examples are all hexamethylene diisocyanate HDI. As a conventional PBAT polymerization process, those skilled in the art usually adjust the type and amount of the chain extender to make the terminal hydroxyl content of the branched PBAT resin after chain extension meet the requirements. The type and amount of the chain extender are exemplarily shown in the examples. The terminal hydroxyl value of the PBAT resin is usually controlled to be less than 15 mol / t, and the number average molecular weight is greater than 80,000 g / mol to meet the degradability requirements of the final product. The chain extension process is a conventional technology. For example, the following process can be used: the PBAT polycondensation viscosity-enhancing product is mixed with hexamethylene diisocyanate HDI, and the amount of HDI added is 4000ppm-8000ppm of the theoretical final product mass. The final polymer is melt-chain extended through a twin-screw extruder (temperature 210-240°C), and the finished product form suitable for sale can be obtained by underwater pelletizing.

[0052] The embodiment of the present invention provides a branched PBAT resin, such as Figure 1 As shown, including PBAT segments (i.e. Figure 1 The PBAT chain structure and branching points include rigid branching points and flexible branching points. By introducing rigid branching points and flexible branching points on the PBAT molecular chain, the melt strength of the material can be improved, thereby increasing the foaming ratio, and also ensuring the degradation performance of the product.

[0053] It should be noted that the branching agent is usually a multi-functional small molecule, which generates branching active points through reaction, and further polymerizes at the branching active points to form a long-chain branched PBAT structure, which significantly improves the melt strength.

[0054] Among them, the rigid branching point is formed by the carboxylic acid compound containing a rigid group entering the molecular chain through an esterification reaction. The structure of the carboxylic acid compound containing a rigid group contains three or more carboxyl groups, and the specific number of carboxyl groups can be three, four, five, etc. The flexible branching point is formed by the hydroxyl compound containing a flexible group entering the molecular chain through an esterification reaction. The structure of the hydroxyl compound containing a flexible group contains three or more hydroxyl groups, and the specific number of hydroxyl groups can be three, four, five, etc.

[0055] In the embodiments of the present invention, a carboxylic acid compound containing a rigid group and having three or more carboxyl groups can form a rigid branched point structure after an esterification reaction, and a hydroxyl compound containing a flexible group and having three or more hydroxyl groups can form a flexible branched point structure after an esterification reaction. Compared with the case of introducing only a rigid branched point structure or a flexible branched point structure, it has better resilience. Specifically, the rigid branched point can enhance the mechanical strength of the cell wall, prevent cell collapse or coalescence, effectively resist external force deformation, and maintain the stability of the cell structure; the flexible branched point can improve the toughness of the cell wall, enable the cells to elastically deform rather than rupture under pressure, increase the mobility of molecular chains, and make the material more easily recover from deformation after being stressed. The combination of the rigid branched point structure and the flexible branched point structure forms a "rigid-flexible combination" dynamic crosslinked network. The rigid part provides support and limits excessive deformation; the flexible part endows elasticity and promotes deformation recovery. This balanced network enables the cells to have both stability and reversible deformation ability, significantly improving the dynamic resilience performance.

[0056] Therefore, in the embodiments of the present invention, by introducing rigid branched points and flexible branched points into the PBAT resin to form a specific branched PBAT resin, the material can simultaneously have excellent foaming performance and degradation performance, and solve the problem that it is difficult to balance the resilience and degradation performance of the PBAT material.

[0057] The mass ratio of the total reaction raw materials of the rigid branched point and the flexible branched point to the reaction product of the branched PBAT resin is at most 0.4:100, that is, less than or equal to 0.4:100. It is appropriate to control the mass of the total reaction raw materials of the rigid branched point and the flexible branched point within the above range. If the total amount of branched points is too much, it will tend to form a crosslinked network structure, resulting in serious damage to the degradation performance.

[0058] The mass ratio of the total reaction raw materials of the rigid branched point and the flexible branched point to the reaction product of the branched PBAT resin is at least 0.2:100, that is, greater than or equal to 0.2:100. Combining with the maximum mass ratio, the mass ratio of the total reaction raw materials of the rigid branched point and the flexible branched point to the reaction product of the branched PBAT resin is (0.2 - 0.4):100, such as 0.20:100, 0.25:100, 0.30:100, 0.35:100, 0.40:100, etc. It is appropriate to control the mass of the total reaction raw materials of the rigid branched point and the flexible branched point within the above range. When the amount of branched points is insufficient, the melt strength will be insufficient. It is appropriate to control the total amount of the rigid branched point and the flexible branched point within the above range to ensure the resilience of the material.

[0059] In some embodiments, further, in the total mass of the reaction raw materials of the rigid branching points and the flexible branching points, the mass proportion of the reaction raw materials of the rigid branching points is 30%-70%, such as 30%, 40%, 50%, 60%, 70%, etc. When the total amount of the reaction raw materials of the rigid branching points and the flexible branching points remains unchanged, the foaming ratio is basically unchanged, but the resilience of the resin formed by branching with only rigid branching points and flexible branching points is significantly improved. It is advisable to control the proportion of the reaction raw materials of the rigid branching points in the total branching point raw materials within the above range, which is conducive to making the comprehensive performance of the resilience performance and the degradation performance reach a better level.

[0060] In some embodiments, the carboxylic acid compounds containing rigid groups that form rigid branching points are selected from at least one of trimesic acid, pyromellitic acid, trimellitic acid, and naphthalenetetracarboxylic acid. The carboxylic acid compounds containing rigid groups can be one or several of the above, all of which can enhance the mechanical strength of the cell wall, prevent cell collapse or coalescence, and can also effectively resist external force deformation and maintain the stability of the cell structure.

[0061] In some embodiments, the hydroxyl compounds containing flexible groups that form flexible branching points can be aliphatic polyols, and the specific types are not limited. In a preferred embodiment, the hydroxyl compounds containing flexible groups are selected from at least one of glycerol, pentaerythritol, xylitol, and sorbitol. The hydroxyl compounds containing flexible groups can be one or several of the above, all of which can improve the toughness of the cell wall and make the material more easily recover from deformation when stressed.

[0062] The branched PBAT resin may also include non-PBAT segment units. The mass ratio of the total reaction raw materials constituting the non-PBAT segment units to the mass of the reaction product of the branched PBAT resin is (0-5):100, such as 0:100, 1:100, 2:100, 3:100, 4:100, 5:100, etc. The total reaction raw materials constituting the non-PBAT segment refer to the flexible segment in the present invention or a new segment structure introduced for other functional modification purposes. The introduction of these non-PBAT segments will affect the degradation ability of the original PBAT segments. Therefore, it is necessary to control the total amount of the introduced non-PBAT segments to ensure that the PBAT segments account for the main part of the resin chain. It should be understood that when no non-PBAT segment units are introduced, the mass percentage of the total reaction raw materials constituting the non-PBAT segment units in the reaction product of the branched PBAT resin is 0%.

[0063] It should be understood that the branching agent and the chain extender do not form chain segment units when entering the PBAT resin, but non-chain segment units, and their end groups are connected to the PBAT chain segment units or other chain segment units; among them, the branching agent has multiple active end groups, which can enable the PBAT polymer to form a branched structure; while the chain extender has two highly active NCO end groups, which are used to increase the molecular weight of PBAT. Its NCO end groups can enable the end groups of two PBAT molecular chains to react with it simultaneously for chain extension, and then obtain the PBAT resin with the target molecular weight. Their contents are very small.

[0064] In some embodiments, the non-PBAT chain segment unit can be a flexible chain segment (i.e., Figure 1 the flexible chain structure in) introduced into the branched PBAT resin as a non-PBAT chain segment. Introducing a flexible chain segment into the PBAT resin can improve the resilience; the flexible chain segment can also enhance the ductility of the molecular chain, and the dynamic crosslinking network formed by its long chain segment and the PBAT chain segment further enhances the resilience of the material. In a preferred embodiment, the flexible chain segment can be a polyether chain segment, and the polyether chain segment is copolymerized into the PBAT chain segment through an ester bond. The polyether chain segment can be copolymerized into the PBAT resin chain segment through an ester bond, which is convenient and easy to operate and can significantly improve the resilience performance of the material. The polyether chain segment is selected from at least one of a polyethylene glycol (PEG) chain segment, a polytetrahydrofuran (PTMEG) chain segment, a polytrimethylene ether glycol (PO3G) chain segment, and a polypropylene glycol (PPG) chain segment. The polyether chain segment can be any one or several of the above. The above several polyether chain segments are all suitable for being introduced as the flexible chain segment in the branched PBAT resin, and all are beneficial to improving the resilience performance of the PBAT resin material.

[0065] In a preferred embodiment, the mass ratio of the total reaction raw materials of the flexible chain segment to the mass of the reaction product of the branched PBAT resin is at least 3:100, such as 3.0:100, 3.5:100, 4.0:100, 4.5:100, 5.0:100, etc. If the proportion of the flexible chain segment is too low, the resilience modification is relatively insufficient. If the proportion of the flexible chain segment is too high, as a non-PBAT chain segment, it will affect the proportion of PBAT in the branched PBAT resin, and then affect the degradation ability of PBAT, causing the resin to lose its degradability.

[0066] In a preferred embodiment, the polyether segment can be a polytetrahydrofuran segment. Introducing a polytetrahydrofuran segment can further improve the resilience performance of the material compared to other polyether segments (such as polyethylene glycol segments, polytrimethylene ether glycol segments, and polypropylene glycol segments). The polytetrahydrofuran segment can be composed of a high molecular weight polytetrahydrofuran segment and a low molecular weight polytetrahydrofuran segment. The number average molecular weight of the high molecular weight polytetrahydrofuran segment is 1800 - 3000 (such as 1800, 2000, 2500, 3000, etc.), and the number average molecular weight of the low molecular weight polytetrahydrofuran segment is 250 - 1000 (such as 250, 500, 800, 1000, etc.); the difference in the number average molecular weights between the high molecular weight polytetrahydrofuran segment and the low molecular weight polytetrahydrofuran segment is greater than or equal to 600, and the difference in their number average molecular weights can be 600, 650, 1000, 1400, 1800, 2000, etc. Two groups of polytetrahydrofurans with different molecular weights are randomly copolymerized into the PBAT segment in the form of an ester bond.

[0067] It should be noted that the low molecular weight polytetrahydrofuran segment (PTMEG) has a shorter segment length and is more inclined to form a partially compatible interface transition region with PBAT, which can reduce the loss modulus (reduce viscous dissipation) and at the same time enhance the adhesion force between the two phases. The high molecular weight PTMEG has a longer segment length and tends to form soft phase microdomains, increasing the storage modulus of the soft phase (enhancing elasticity) and providing a driving force for elastic recovery. The soft segment gradient phase separation structure (hard segment - transition region - soft segment) formed by the molecular weight difference can store and release energy more efficiently, evenly disperse external forces, and avoid the rupture of the cell wall or plastic deformation caused by excessive local stress, thereby improving the overall flexibility and resilience efficiency of the material.

[0068] Furthermore, the mass ratio of the reaction raw materials constituting the high molecular weight polytetrahydrofuran segment in the total amount of the reaction raw materials constituting the polytetrahydrofuran segment is 20% - 80%, such as 20%, 30%, 40%, 50%, 60%, 70%, 80%, etc. Since the total amount of PTMEG accounts for a relatively small proportion, it has a relatively small impact on the copolymer melt, so the foaming ratio remains basically unchanged.

[0069] The PBAT segment is formed by the reaction of adipic acid, terephthalic acid, and 1,4 - butanediol. The ratio of adipic acid to terephthalic acid needs to be controlled within a certain range to make the PBAT resin meet the international biodegradable requirements. To meet the international biodegradable requirements, in the PBAT segment, the molar ratio of adipic acid units to terephthalic acid units is (51 - 55):(45 - 49), such as 51:49, 52:48, 53:47, 54:46, 55:45, etc.

[0070] The hydroxyl - end - group content of the branched PBAT resin provided by the embodiments of the present invention is less than or equal to 15 mol / t, such as 15 mol / t, 14 mol / t, 13 mol / t, 12 mol / t, 11 mol / t, etc.; the number - average molecular weight of the branched PBAT resin is greater than 80000 g / mol, such as 81000 g / mol, 82000 g / mol, 84000 g / mol, 85000 g / mol, 87000 g / mol, 89000 g / mol, 90000 g / mol, etc.

[0071] The embodiments of the present invention also provide a preparation method of a branched PBAT resin, using adipic acid, terephthalic acid, 1,4 - butanediol, chain extender, branching agent as main raw materials to prepare the branched PBAT resin; wherein, the branching agent includes a carboxylic - acid - type compound containing a rigid group and a hydroxyl - type compound containing a flexible group.

[0072] It should be noted that the carboxylic - acid - type compound containing a rigid group is used as a rigid branching agent, and the hydroxyl - type compound containing a flexible group is used as a flexible branching agent. The combination of the two can form a "rigid - flexible combination" dynamic cross - linked network. The rigid part provides support and restricts excessive deformation; the flexible part endows elasticity and promotes deformation recovery. This balanced network enables the cell to have both stability and reversible deformation ability, significantly improving the dynamic resilience performance.

[0073] In some embodiments, the preparation process includes esterification, polycondensation, and chain extension in sequence; among them, the esterification can be direct esterification or transesterification, both of which can prepare a branched PBAT resin with excellent foaming performance and degradation performance.

[0074] The following is an illustration using the transesterification method, which is more widely used in industrial applications. The preparation steps are as follows:

[0075] S1. Parallel esterification

[0076] Parallel esterification includes two steps: A - esterification and T - esterification. A - esterification is the reaction of adipic acid (AA) and 1,4 - butanediol (BDO), and T - esterification is the reaction of terephthalic acid (PTA) and 1,4 - butanediol.

[0077] The steps of A esterification in the embodiments of the present invention: Adipic acid, 1,4-butanediol and a hydroxyl compound containing a flexible group (such as an aliphatic polyol) are mixed and reacted to obtain a first esterification product. The temperature of T esterification is higher than that of A esterification, while the thermal stability of the aliphatic polyol is poor, and it is suitable for reaction under low-temperature esterification conditions to form a stable ester bond structure. During the preparation of the first esterification product, the molar ratio of adipic acid to 1,4-butanediol is controlled to be 1:(1.1 - 1.4), such as 1:1.1, 1:1.2, 1:1.3, 1:1.4, etc., so that 1,4-butanediol is in excess to ensure complete esterification. In A esterification, the reaction conditions are controlled to make the esterification rate greater than 90% to ensure the smooth progress of subsequent reactions.

[0078] The steps of T esterification in the embodiments of the present invention: Terephthalic acid (PTA), 1,4-butanediol, a carboxylic acid compound containing a rigid group, a non-PBAT chain segment compound and an esterification catalyst are mixed and reacted to obtain a second esterification product. The carboxylic acid compounds containing rigid groups are mostly aromatic polyacids with low reaction activity, and are suitable for reaction under high-temperature esterification conditions to form a stable ester bond structure. The molar ratio of terephthalic acid (PTA) to 1,4-butanediol is 1:(1.6 - 2.2), such as 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, etc., so that 1,4-butanediol is in excess to ensure complete esterification. During T esterification, the reaction conditions are controlled to ensure that the esterification rate of the reactants exceeds 95% to ensure the smooth progress of subsequent reactions.

[0079] It should be noted that for the specific dosages of the hydroxyl compound containing a flexible group, the carboxylic acid compound containing a rigid group, and the flexible chain segment compound, refer to the introduction of the branched PBAT resin and will not be repeated here.

[0080] S2. Mixed transesterification

[0081] The first esterification product and the second esterification product are mixed and reacted to make the two esterification products fully transesterify to form an esterification intermediate.

[0082] S3. Polycondensation

[0083] The esterification intermediate is polycondensed to make the number-average molecular weight reach 16,000 - 25,000 (such as 16,000, 18,000, 20,000, 22,000, 25,000, etc.). Through polycondensation, the number-average molecular weight at this stage meets the requirements, and the degree of polymerization of the reactants is increased to 80 - 120.

[0084] S4. Chain extension

[0085] The polycondensation and viscosity-increasing product is mixed and reacted with a chain extender to obtain a polymer with a terminal carboxyl content of less than 15 mol / t and a number-average molecular weight of greater than 80,000 g / mol. After chain extension with the chain extender, a final polymer with a terminal carboxyl content and a number-average molecular weight meeting the requirements is obtained.

[0086] It should be noted that the preparation method of the branched PBAT resin provided by the present invention can prepare a highly elastic and degradable PBAT, which can achieve a molecular chain with an LCB structure and no chemical cross-linking. There is only a reversible dynamic cross-linking network in the product, and the melt strength of the product can be increased by more than 30%, and the compression deformation can be reduced by more than 20%.

[0087] The embodiment of the present invention also provides a preparation method of a foam material, which is prepared by using the branched PBAT resin provided by the embodiment of the present invention. Since the branched PBAT resin has excellent foaming performance and degradation performance at the same time, the foaming ratio of the prepared foam material is higher and the degradability is more excellent.

[0088] In some embodiments, the preparation process includes: subjecting the branched PBAT resin to high-pressure impregnation with a supercritical gas, and then relieving the pressure to form a closed-cell foam material. The supercritical gas can be supercritical carbon dioxide, but is not limited thereto. The operating pressure of the high-pressure impregnation is 15 MPa - 25 MPa, such as 15 MPa, 18 MPa, 20 MPa, 23 MPa, 25 MPa, etc.; the operating temperature can be 100 °C, 105 °C, 110 °C, 115 °C, 120 °C, etc.; the impregnation time is 2 h - 4 h, such as 2 h, 3 h, 4 h, etc. When relieving the pressure, a rapid pressure relief method is adopted, and the pressure relief speed is 5 MPa / s - 10 MPa / s, such as 5 MPa / s, 6 MPa / s, 7 MPa / s, 8 MPa / s, 9 MPa / s, 10 MPa / s, etc.

[0089] It should be noted that by using the branched PBAT resin provided by the embodiment of the present invention to prepare a closed-cell foam material, a foam material with a high foaming ratio and good degradability can be obtained through a simple process of high-pressure impregnation and rapid pressure relief.

[0090] The embodiment of the present invention also provides a foam material, which is prepared by using the preparation method of the foam material provided by the embodiment of the present invention. The foaming ratio of the foam material is 20 - 25 times, the falling ball rebound rate ≥ 75%, and the degradation rate after 180 days > 90%. The foam material provided by the embodiment of the present invention has the characteristics of a high foaming ratio and excellent degradability, can fully balance the foaming performance and degradation performance of the material, and has a very good application prospect.

[0091] The features and properties of the present invention will be further described in detail below in conjunction with the embodiments.

[0092] It should be noted that the test methods for the relevant structures and performance parameters involved in the following examples or comparative examples are as follows:

[0093] 1. Test method for the content of terminal carboxyl groups: Refer to the method specified in Section 4.8 of GB / T 32366-2015 Biodegradable Poly(butylene terephthalate-co-adipate) (PBAT).

[0094] 2. Test method for number-average molecular weight: Refer to the methods specified in GB / T 36214.1-2018 and GB / T 36214.2-2018 for testing the number-average molecular weight. Test instrument: Waters 1515, detector: Waters 2414, chromatographic column: PL1110-6100 & PL1110-6500, mobile phase: dichloromethane, test temperature: 40 °C, flow rate: 1 mL / min, standard sample: PS.

[0095] 3. Test methods for foaming performance and degradation performance:

[0096] (1) Preparation of closed-cell foam materials: Immerse the PBAT resin prepared in the examples or comparative examples in supercritical CO2 in an autoclave, and then rapidly release the pressure to form closed-cell foam materials. Among them, the pressure of the autoclave is 20 MPa, the temperature is 110 °C, the impregnation time is 3 h, and the pressure release rate is 10 MPa / s.

[0097] (2) Test for density and foaming ratio: Refer to the method specified in ATSM-3574-TEST-A. Foaming ratio = density of unfoamed sample / density of foamed sample, and the calculation result of the foaming ratio is rounded to an integer value.

[0098] (3) Ball drop rebound rate: Refer to the method specified in the ball drop rebound test of ATSM-D-3574-H.

[0099] (4) Test for 180-day soil degradation rate: Refer to the method specified in Section 1 of GB / T 19277.1-2011 Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions - Method by measuring the evolved carbon dioxide. The reference is TLC cellulose, the volume of the compost glass container is 3 L, the compost temperature is kept constant at 58 ± 1 °C, and the dry weight ratio of the test sample to the fertilizer is 1:6.

[0100] It should be noted that the following examples are converted to the addition amounts of each component according to the final product yield of 10 Kg.

[0101] Example 1

[0102] This example provides a preparation method of a branched PBAT resin, and the steps are as follows:

[0103] (1) Parallel esterification

[0104] A Esterification: 23.87 mol of adipic acid (AA) was mixed with 26.25 mol of 1,4-butanediol (BDO), i.e., the mixing molar ratio was 1:1.1, and 10 g of the branching agent pentaerythritol (denoted as the flexible branching point reaction raw material) was added for reaction; the reaction process parameters were adjusted to ensure that the esterification rate of the reactants was ≥90%, which was the conventional A esterification control requirement in the preparation of PBAT. In this example, the reaction temperature at this stage was controlled at 210 °C, the reaction pressure was maintained at 100 kPa(A), and the reaction time was 4 h to obtain the A esterification product.

[0105] T Esterification: 22.03 mol of terephthalic acid (PTA) was mixed with 39.65 mol of 1,4-butanediol (BDO), i.e., the mixing molar ratio was 1:1.8, and the molar ratio of AA used in A esterification to PTA used in T esterification was 52:48. At the same time, 10 g of the branching agent pyromellitic acid (denoted as the rigid branching point reaction raw material) and 300 g of polytetrahydrofuran (denoted as the flexible segment reaction raw material) (the number average molecular weight of 2000 and 1000 was compounded according to the mass ratio of 2:1) and the T esterification catalyst were added; the reaction process parameters were adjusted to ensure that the esterification rate of the reactants was ≥95%, which was the conventional T esterification control requirement in the preparation of PBAT. The reaction temperature was controlled at 240 °C, the reaction pressure was maintained at 50 kPa(A), and the reaction time was 4 h to ensure that the esterification rate of the reactants exceeded 95% to obtain the T esterification product.

[0106] (2) Mixed transesterification

[0107] The A esterification product and the T esterification product were subjected to a mixed reaction, and the reaction process parameters were adjusted to ensure that the esterification rate of the reactants was ≥98.5%, which was the conventional transesterification control requirement in the preparation of PBAT. In this example, the reaction temperature at this stage was controlled at 240 °C, the reaction pressure was maintained at 60 kPa(A), and the reaction time was 3 h.

[0108] (3) Polycondensation

[0109] A polycondensation catalyst was added to the mixed transesterification product, and the reaction process parameters were adjusted to ensure that the number average molecular weight of the reactants reached 16,000 - 25,000. In this example, the reaction temperature was controlled at 235 °C, the reaction pressure was maintained at 150 Pa(A), and the reaction time was 5 h. At this stage, the excess BDO was extracted.

[0110] (4) Chain extension

[0111] Chain extension and pelletizing: The PBAT end polycondensation product was mixed with 50 g of the chain extender (hexamethylene diisocyanate HDI), and melt chain extension extrusion and pelletizing were carried out through a twin-screw extruder (temperature 220 °C) to obtain 10 Kg of product.

[0112] In the prepared branched PBAT resin, the feeding amount of the flexible branching point reaction raw material accounts for the mass ratio of the final product as 0.1:100, the feeding amount of the rigid branching point reaction raw material accounts for the mass ratio of the final product as 0.1:100, the total reaction raw material of the branching point accounts for the mass ratio of the final product as 0.2:100, the mass proportion of the rigid branching point reaction raw material in the total mass of the branching point total reaction raw material is 50%, the total feeding mass of the flexible chain segment accounts for the mass ratio of the final product as 3:100, the end carboxyl group content of the finally prepared branched PBAT resin is 14.5 mol / t, and the number average molecular weight is 89,650 g / mol.

[0113] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.053 g / cm 3 , and the falling ball rebound rate is 76%; the degradation performance: the soil degradation rate in 180 days is 93%.

[0114] Example 2

[0115] This example provides a preparation method of a branched PBAT resin, and the steps are as follows:

[0116] (1) Parallel esterification

[0117] A esterification: Mix 23.07 mol of adipic acid (AA) with 27.68 mol of 1,4-butanediol (BDO), that is, the mixing molar ratio is 1:1.2, and add 12 g of the branching agent sorbitol (denoted as the flexible branching point reaction raw material) to react; adjust the reaction process parameters to ensure that the esterification rate of the reactants ≥ 90%, which is the conventional A esterification control requirement in PBAT preparation. In this example, the reaction temperature in this stage is controlled at 210 °C, the reaction pressure is maintained at 100 kPa(A), and the reaction time is 4 h to obtain the A esterification product.

[0118] T esterification: Mix 22.16 mol of terephthalic acid (PTA) with 35.46 mol of 1,4-butanediol (BDO), that is, the mixing molar ratio is 1:1.6, the molar ratio of AA used in A esterification to PTA used in T esterification is 51:49, and at the same time add 28 g of the branching agent trimesic acid (denoted as the rigid branching point reaction raw material) and 400 g of polytetrahydrofuran (denoted as the flexible chain segment reaction raw material) (the number average molecular weight is 1800 and 250 are compounded according to the mass ratio of 4:1), and the T esterification catalyst; adjust the reaction process parameters to ensure that the esterification rate of the reactants ≥ 95%, which is the conventional T esterification control requirement in PBAT preparation. The reaction temperature is controlled at 240 °C, the reaction pressure is maintained at 50 kPa(A), and the reaction time is 4 h to ensure that the esterification rate of the reactants exceeds 95% to obtain the T esterification product.

[0119] (2) Mixed transesterification

[0120] Mix the esterification product of A and the esterification product of T, and adjust the reaction process parameters to ensure that the esterification rate of the reactants is ≥98.5%. This is the conventional transesterification control requirement in the preparation of PBAT. In this example, the reaction temperature at this stage is controlled at 240 °C, the reaction pressure is maintained at 60 kPa(A), and the reaction time is 3 h.

[0121] (3) Polycondensation

[0122] Add a polycondensation catalyst to the mixed transesterification product, and adjust the reaction process parameters to ensure that the number-average molecular weight of the reactants reaches 16,000 - 25,000. In this example, the reaction temperature is controlled at 235 °C, the reaction pressure is maintained at 150 Pa(A), and the reaction time is 5 h. At this stage, the excess BDO is withdrawn.

[0123] (4) Chain extension

[0124] Chain extension and pelletizing: Mix the final polycondensation product of PBAT with 60 g of a chain extender (hexamethylene diisocyanate HDI), and perform melt chain extension extrusion and pelletizing through a twin-screw extruder (temperature 220 °C) to obtain 10 Kg of product.

[0125] In the prepared branched PBAT resin, the feeding amount of the reaction raw material of the flexible branching point accounts for the mass ratio of the final product as 0.12:100, the feeding amount of the reaction raw material of the rigid branching point accounts for the mass ratio of the final product as 0.28:100, the total reaction raw material of the branching point accounts for the mass ratio of the final product as 0.4:100, the mass of the reaction raw material of the rigid branching point in the total mass of the reaction raw materials of the branching point accounts for 70%, the total feeding mass of the flexible chain segments accounts for the mass ratio of the final product as 4:100, and the end carboxyl group content of the finally prepared branched PBAT resin is 13.8 mol / t, and the number-average molecular weight is 93,296 g / mol.

[0126] The foaming performance of the prepared PBAT resin: the foaming ratio is 24 times, the density is 0.043 g / cm 3 , and the falling ball rebound rate is 79%; the degradation performance: the soil degradation rate in 180 days is 91%.

[0127] Example 3

[0128] This example provides a method for preparing a branched PBAT resin, and the steps are as follows:

[0129] (1) Parallel esterification

[0130] A Esterification: 24.82 mol of adipic acid (AA) and 32.26 mol of 1,4-butanediol (BDO) were mixed, i.e., the mixing molar ratio was 1:1.3, and 21 g of the branching agent xylitol (denoted as the flexible branching point reaction raw material) was added for reaction; the reaction process parameters were adjusted to ensure that the esterification rate of the reactants was ≥90%, which was the conventional A esterification control requirement in the preparation of PBAT. In this example, the reaction temperature at this stage was controlled at 210 °C, the reaction pressure was maintained at 100 kPa(A), and the reaction time was 4 h to obtain the A esterification product.

[0131] T Esterification: 21.14 mol of terephthalic acid (PTA) and 42.28 mol of 1,4-butanediol (BDO) were mixed, i.e., the mixing molar ratio was 1:2.0, and the molar ratio of AA used in A esterification to PTA used in T esterification was 54:46. At the same time, 9 g of the branching agent naphthalenetetracarboxylic acid (denoted as the rigid branching point reaction raw material) and 300 g of polytetrahydrofuran (denoted as the flexible segment reaction raw material) (the number average molecular weights of 1800 and 650 were compounded at a mass ratio of 1:2) and the T esterification catalyst were added; the reaction process parameters were adjusted to ensure that the esterification rate of the reactants was ≥95%, which was the conventional T esterification control requirement in the preparation of PBAT. The reaction temperature was controlled at 240 °C, the reaction pressure was maintained at 50 kPa(A), and the reaction time was 4 h to ensure that the esterification rate of the reactants exceeded 95% to obtain the T esterification product.

[0132] (2) Mixed transesterification

[0133] The A esterification product and the T esterification product were subjected to a mixed reaction, and the reaction process parameters were adjusted to ensure that the esterification rate of the reactants was ≥98.5%, which was the conventional transesterification control requirement in the preparation of PBAT. In this example, the reaction temperature at this stage was controlled at 240 °C, the reaction pressure was maintained at 60 kPa(A), and the reaction time was 3 h.

[0134] (3) Polycondensation

[0135] A polycondensation catalyst was added to the mixed transesterification product, and the reaction process parameters were adjusted to ensure that the number average molecular weight of the reactants reached 16,000 - 25,000. In this example, the reaction temperature was controlled at 235 °C, the reaction pressure was maintained at 150 Pa(A), and the reaction time was 5 h. At this stage, the excess BDO was extracted.

[0136] (4) Chain extension

[0137] Chain extension and pelletizing: The PBAT end polycondensation product was mixed with 45 g of the chain extender (hexamethylene diisocyanate HDI), and melt chain extension extrusion and pelletizing were carried out through a twin-screw extruder (temperature 220 °C) to obtain 10 Kg of products.

[0138] In the prepared branched PBAT resin, the feeding amount of the flexible branching point reaction raw material accounts for the mass ratio of the final product as 0.21:100, the feeding amount of the rigid branching point reaction raw material accounts for the mass ratio of the final product as 0.09:100, the total reaction raw material of the branching point accounts for the mass ratio of the final product as 0.3:100, the mass ratio of the rigid branching point reaction raw material in the total reaction raw material mass of the branching point is 30%, the total feeding mass of the flexible chain segment accounts for the mass ratio of the final product as 3:100, the end carboxyl group content of the finally prepared branched PBAT resin is 14.9 mol / t, and the number average molecular weight is 80024 g / mol.

[0139] The foaming performance of the prepared PBAT resin: the foaming ratio is 22 times, and the density is 0.048 g / cm 3 , and the falling ball rebound rate is 77%; the degradation performance: the soil degradation rate in 180 days is 92%.

[0140] Example 4

[0141] This example provides a preparation method of a branched PBAT resin, and the steps are as follows:

[0142] (1) Parallel esterification

[0143] A esterification: Mix 24.70 mol of adipic acid (AA) with 34.58 mol of 1,4-butanediol (BDO), that is, the mixing molar ratio is 1:1.4, and add 20 g of the branching agent glycerol (denoted as the flexible branching point reaction raw material) to react; adjust the reaction process parameters to ensure that the esterification rate of the reactants ≥ 90%, which is the conventional A esterification control requirement in PBAT preparation. In this example, the reaction temperature in this stage is controlled at 210 °C, the reaction pressure is maintained at 100 kPa(A), and the reaction time is 4 h to obtain the A esterification product.

[0144] T esterification: Mix 20.21 mol of terephthalic acid (PTA) with 44.46 mol of 1,4-butanediol (BDO), that is, the mixing molar ratio is 1:2.2, the molar ratio of AA used in A esterification to PTA used in T esterification is 55:45, and at the same time add 20 g of the branching agent trimellitic acid (denoted as the rigid branching point reaction raw material) and 500 g of polytetrahydrofuran (denoted as the flexible chain segment reaction raw material) (the number average molecular weight of 3000 and 1000 is compounded according to the mass ratio of 1:4), and the T esterification catalyst; adjust the reaction process parameters to ensure that the esterification rate of the reactants ≥ 95%, which is the conventional T esterification control requirement in PBAT preparation. The reaction temperature is controlled at 240 °C, the reaction pressure is maintained at 50 kPa(A), and the reaction time is 4 h to ensure that the esterification rate of the reactants exceeds 95% to obtain the T esterification product.

[0145] (2) Mixed transesterification

[0146] Mix the esterification product of A and the esterification product of T, and adjust the reaction process parameters to ensure that the esterification rate of the reactants is ≥98.5%. This is the conventional transesterification control requirement in the preparation of PBAT. In this example, the reaction temperature at this stage is controlled at 240°C, the reaction pressure is maintained at 60 kPa(A), and the reaction time is 3 h.

[0147] (3) Polycondensation

[0148] Add a polycondensation catalyst to the mixed transesterification product, and adjust the reaction process parameters to ensure that the number-average molecular weight of the reactants reaches 16,000 - 25,000. In this example, the reaction temperature is controlled at 235°C, the reaction pressure is maintained at 150 Pa(A), and the reaction time is 5 h. At this stage, the excess BDO is drawn out.

[0149] (4) Chain extension

[0150] Chain extension and pelletizing: Mix the final polycondensation product of PBAT with 65 g of a chain extender (hexamethylene diisocyanate HDI), and carry out melt chain extension and extrusion granulation through a twin-screw extruder (temperature 220°C) to obtain 10 Kg of product.

[0151] In the prepared branched PBAT resin, the feeding amount of the flexible branching point reaction raw material accounts for the mass ratio of the final product as 0.2:100, the feeding amount of the rigid branching point reaction raw material accounts for the mass ratio of the final product as 0.2:100, the total reaction raw material of the branching point accounts for the mass ratio of the final product as 0.4:100, the mass of the rigid branching point reaction raw material in the total reaction raw material mass of the branching point accounts for 50%, the total feeding mass of the flexible chain segments accounts for the mass ratio of the final product as 5:100, and the end carboxyl group content of the finally prepared branched PBAT resin is 13 mol / t, and the number-average molecular weight is 10223 g / mol.

[0152] The foaming performance of the prepared PBAT resin: The foaming ratio is 24 times, the density is 0.044 g / cm 3 , and the falling ball rebound rate is 80%; Degradation performance: The soil degradation rate in 180 days is 90%.

[0153] Example 5

[0154] The difference from Example 1 is only that: only the dosages of the flexible branching point reaction raw material and the rigid branching point reaction raw material are changed. Specifically as follows: The feeding amount of the flexible branching point reaction raw material accounts for the mass ratio of the final product as 0.05:100, the feeding amount of the rigid branching point reaction raw material accounts for the mass ratio of the final product as 0.05:100, and the total reaction raw material of the branching point accounts for the mass ratio of the final product as 0.1:100.

[0155] The terminal carboxyl group content of the branched PBAT resin finally obtained in this example is 14.4 mol / t, and the number average molecular weight is 89,954 g / mol.

[0156] The foaming performance of the prepared PBAT resin: the foaming ratio is 18 times, and the density is 0.058 g / cm 3 , and the falling ball rebound rate is 70%; the degradation performance: the soil degradation rate in 180 days is 94%.

[0157] Comparing Example 1 and Example 5, it can be seen that when the branching points are insufficient, the melt strength will be insufficient, manifested as a decrease in the foaming ratio and a decrease in the rebound performance; however, the foaming ratio of 18 times is still at an appropriate level.

[0158] Example 6

[0159] The difference from Example 1 is only that: the feeding amount of the flexible segment reaction raw material is different, specifically as follows: the total feeding mass ratio of the flexible segment to the mass of the final product is 1:100.

[0160] The terminal carboxyl group content of the branched PBAT resin finally obtained in this example is 14.9 mol / t, and the number average molecular weight is 86,135 g / mol.

[0161] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.052 g / cm 3 , and the falling ball rebound rate is 70%; the degradation performance: the soil degradation rate in 180 days is 95%.

[0162] Comparing Example 1 and Example 6, it can be seen that when the proportion of the flexible segment is low, the rebound modification effect decreases.

[0163] Example 7

[0164] The difference from Example 1 is only that: polytetrahydrofuran uses a single molecular weight raw material, and the number average molecular weight is 2000.

[0165] The terminal carboxyl group content of the branched PBAT resin finally obtained in this example is 14.5 mol / t, and the number average molecular weight is 89,732 g / mol.

[0166] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.053 g / cm 3 , and the falling ball rebound rate is 74%; the degradation performance: the soil degradation rate in 180 days is 93%.

[0167] Example 8

[0168] The difference from Example 1 is only that: polytetrahydrofuran uses a single molecular weight raw material, and the number average molecular weight is 1000.

[0169] The terminal carboxyl group content of the branched PBAT resin finally obtained in this example is 14.5 mol / t, and the number average molecular weight is 89412 g / mol.

[0170] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.052 g / cm 3 , and the falling ball rebound rate is 75%; the degradation performance: the soil degradation rate in 180 days is 93%.

[0171] Comparing Comparative Example 1 with Examples 7-8, it can be seen that the scheme of compounding polytetrahydrofuran with different molecular weights can improve the rebound performance compared with using raw materials with a single molecular weight.

[0172] Example 9

[0173] The difference from Example 8 is only that: polytetrahydrofuran is replaced with an equal amount of polyethylene glycol with a number average molecular weight of 1000.

[0174] The terminal carboxyl group content of the branched PBAT resin finally obtained in this example is 13 mol / t, and the number average molecular weight is 85987 g / mol.

[0175] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.053 g / cm 3 , and the falling ball rebound rate is 72%; the degradation performance: the soil degradation rate in 180 days is 93%.

[0176] Comparing Example 8 with Example 9, it can be seen that using polytetrahydrofuran in Example 8 can significantly improve the rebound performance compared with using polyethylene glycol in Example 9.

[0177] Example 10

[0178] The difference from Example 1 is only that: no polytetrahydrofuran is added.

[0179] The terminal carboxyl group content of the branched PBAT resin finally obtained in this example is 16.5 mol / t, and the number average molecular weight is 83230 g / mol.

[0180] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.053 g / cm 3 , and the falling ball rebound rate is 68%; the degradation performance: the soil degradation rate in 180 days is 96%.

[0181] Comparing Example 1 with Example 10, it can be seen that if the flexible chain segment is not added, the degradation performance can be improved to a certain extent, but the rebound performance decreases, and the overall performance is still relatively excellent.

[0182] Comparative Example 1

[0183] The difference from Example 10 is only that: pentaerythritol and pyromellitic acid are not added.

[0184] The carboxyl end group content of the branched PBAT resin finally obtained in this comparative example is 17 mol / t, and the number-average molecular weight is 79783 g / mol.

[0185] The foaming performance of the prepared PBAT resin: the foaming ratio is 16 times, and the density is 0.065 g / cm 3 , and the falling ball rebound rate is 62%; the degradation performance: the soil degradation rate in 180 days is 98%.

[0186] Comparative Example 2

[0187] The difference from Example 10 is only that: pyromellitic acid is not added and is replaced with an equal amount of pentaerythritol.

[0188] The carboxyl end group content of the branched PBAT resin finally obtained in this comparative example is 16.3 mol / t, and the number-average molecular weight is 84213 g / mol.

[0189] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.052 g / cm 3 , and the falling ball rebound rate is 63%; the degradation performance: the soil degradation rate in 180 days is 97%.

[0190] Comparative Example 3

[0191] The difference from Example 10 is only that: pentaerythritol is not added and is replaced with an equal amount of pyromellitic acid.

[0192] The carboxyl end group content of the branched PBAT resin finally obtained in this comparative example is 16.6 mol / t, and the number-average molecular weight is 85034 g / mol.

[0193] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.053 g / cm 3 , and the falling ball rebound rate is 63%; the degradation performance: the soil degradation rate in 180 days is 96%.

[0194] It can be seen from Example 10 and Comparative Examples 1-3 that introducing a branching point can improve the foaming ratio. At the same level of foaming ratio, introducing both a flexible branching point and a rigid branching point can significantly improve the rebound performance. If only a flexible branching point or a rigid branching point is introduced, the rebound performance cannot be better improved. When the mass ratio of the reaction raw materials of the rigid branching point in the total reaction raw material mass of the rigid branching point and the flexible branching point is 30%-70%, sufficient rigid parts can be obtained to limit excessive deformation; sufficient flexible parts can be obtained to promote deformation recovery, so that the foam cells have both stability and reversible deformation ability, and the rebound performance can be better improved.

[0195] Comparative Example 4

[0196] The difference from Example 1 is only that: only the amounts of the flexible branching point reaction raw materials and the rigid branching point reaction raw materials are changed, specifically as follows: the feeding amount of the flexible branching point reaction raw materials accounts for the mass ratio of the final product of 0.25:100, the feeding amount of the rigid branching point reaction raw materials accounts for the mass ratio of the final product of 0.25:100, and the total reaction raw materials of the branching points account for the mass ratio of the final product of 0.5:100.

[0197] The carboxyl end group content of the branched PBAT resin finally prepared in this comparative example is 14.6 mol / t, and the number average molecular weight is 89153 g / mol.

[0198] The foaming performance of the prepared PBAT resin: the foaming ratio is 25 times, and the density is 0.042 g / cm 3 , and the falling ball rebound rate is 79%; the degradation performance: the soil degradation rate in 180 days is 87%.

[0199] Comparing Example 1 and Comparative Example 4, it can be seen that too much total amount of branching points will cause cross-linking and seriously damage the degradation performance. When the total amount of branching points increases, cross-linking is likely to occur, resulting in a significant decrease in the degradation performance; therefore, the total amount of branching points needs to be controlled within a reasonable range, and the mass ratio of the total reaction raw materials of the rigid branching point and the flexible branching point to the reaction product of the branched PBAT resin is (0.1-0.4):100, preferably (0.2-0.4):100.

[0200] Comparative Example 5

[0201] The difference from Example 1 is only that: the feeding amount of the flexible chain segment reaction raw materials is different, specifically as follows: the total feeding mass of the flexible chain segment accounts for the mass ratio of the final product of 8:100.

[0202] The carboxyl end group content of the branched PBAT resin finally prepared in this comparative example is 13 mol / t, and the number average molecular weight is 89324 g / mol.

[0203] The foaming performance of the prepared PBAT resin: the foaming ratio is 20 times, and the density is 0.052 g / cm 3 , and the falling ball rebound rate is 82%; the degradation performance: the soil degradation rate in 180 days is 85%.

[0204] Comparing Example 1 and Comparative Example 5, it can be seen that if the proportion of the flexible chain segment is too high, the branched PBAT resin will lose its degradability.

Claims

1. A branched PBAT resin, characterized in that, It includes PBAT chain segment units and branching points; The branching points include rigid branching points and flexible branching points, and the total mass of the reaction raw materials of the rigid branching points and the flexible branching points accounts for at most 0.4:100 of the mass of the reaction product of the branched PBAT resin; Among them, the rigid branching points are formed by the carboxylic acid compounds containing rigid groups entering the molecular chain through esterification reaction, and the structure of the carboxylic acid compounds containing rigid groups contains three or more carboxyl groups; The flexible branching points are formed by the hydroxyl compounds containing flexible groups entering the molecular chain after esterification reaction, and the structure of the hydroxyl compounds containing flexible groups contains three or more hydroxyl groups; The branched PBAT resin also includes non-PBAT chain segment units, and the total mass of the reaction raw materials constituting the non-PBAT chain segment units accounts for (0-5):100 of the mass of the reaction product of the branched PBAT resin; 2. The branched PBAT resin according to claim 1, wherein The total mass of the reaction raw materials of the rigid branching points and the flexible branching points accounts for at least 0.2:100 of the mass of the reaction product of the branched PBAT resin; And / or, in the total mass of the reaction raw materials of the rigid branching points and the flexible branching points, the mass proportion of the reaction raw materials of the rigid branching points is 30%-70%; And / or, the carboxylic acid compounds containing rigid groups forming the rigid branching points are selected from at least one of trimellitic acid, pyromellitic acid, trimellitic anhydride and naphthalenetetracarboxylic acid; And / or, the hydroxyl compounds containing flexible groups forming the flexible branching points are aliphatic polyols; preferably, the hydroxyl compounds containing flexible groups are selected from at least one of glycerol, pentaerythritol, xylitol and sorbitol; 3. The branched PBAT resin according to claim 1, characterized in that, The non-PBAT chain segment units are flexible chain segments; preferably, the flexible chain segments are polyether chain segments, and the polyether chain segments are copolymerized into the PBAT chain segments in the form of ester bonds; more preferably, the polyether chain segments are selected from at least one of polyethylene glycol chain segments, polytetrahydrofuran chain segments, polytrimethylene ether glycol chain segments and polypropylene glycol chain segments; The mass ratio of the total reaction raw materials of the flexible chain segments to the reaction product of the branched PBAT resin is (3-5):100; 4. The branched PBAT resin according to claim 3, characterized in that, The polyether chain segment is a polytetrahydrofuran chain segment; Preferably, the polytetrahydrofuran chain segment is composed of a high molecular weight polytetrahydrofuran chain segment and a low molecular weight polytetrahydrofuran chain segment; the number average molecular weight of the high molecular weight polytetrahydrofuran chain segment is 1800-3000, and the number average molecular weight of the low molecular weight polytetrahydrofuran chain segment is 250-1000; the difference in the number average molecular weight between the high molecular weight polytetrahydrofuran chain segment and the low molecular weight polytetrahydrofuran chain segment is greater than or equal to 600; More preferably, the mass proportion of the reaction raw materials constituting the high molecular weight polytetrahydrofuran chain segment in the total amount of the reaction raw materials constituting the polytetrahydrofuran chain segment is 20%-80%; 5. The branched PBAT resin according to any one of claims 1-4, characterized in that In the PBAT chain segment, the molar ratio of adipic acid units to terephthalic acid units is (51-55):(45-49); And / or, the terminal hydroxyl group content of the branched PBAT resin is less than or equal to 15 mol / t; And / or, the number-average molecular weight of the branched PBAT resin is greater than 80,000 g / mol.

6. A method for preparing the branched PBAT resin according to any one of claims 1-5, characterized in that, Comprising: Using adipic acid, terephthalic acid, 1,4-butanediol, chain extender, and branching agent as main raw materials to prepare the branched PBAT resin; Wherein, the branching agent includes a carboxylic acid compound containing a rigid group and a hydroxyl compound containing a flexible group.

7. The preparation method according to claim 6, wherein Including esterification, polycondensation, and chain extension in sequence; among them, the esterification is carried out by the transesterification method or the direct esterification method; Preferably, the preparation process includes: Parallel esterification: Mix and react adipic acid, 1,4-butanediol, and the hydroxyl compound containing a flexible group to obtain a first esterification product; mix and react terephthalic acid, 1,4-butanediol, the carboxylic acid compound containing a rigid group, a non-PBAT chain segment compound, and an esterification catalyst to obtain a second esterification product; Mixed transesterification: Mix and react the first esterification product and the second esterification product to obtain an esterification intermediate; Polycondensation: Carry out polycondensation on the esterification intermediate to make the number-average molecular weight reach 16,000 - 25,000 to obtain a polycondensation viscosity-increasing product; Chain extension: Mix and react the polycondensation viscosity-increasing product with a chain extender to obtain a polymer with a terminal carboxyl group content lower than 15 mol / t and a number-average molecular weight greater than 80,000 g / mol.

8. The preparation method according to claim 7, wherein During the preparation of the first esterification product, control the molar ratio of adipic acid to 1,4-butanediol to be 1:(1.1 - 1.4), and control the esterification rate to be greater than 90%; Preferably, during the preparation of the second esterification product, control the molar ratio of terephthalic acid to 1,4-butanediol to be 1:(1.6 - 2.2), and control the esterification rate to be greater than 95%.

9. A method for preparing a foam material, characterized in that, Prepared using the branched PBAT resin according to any one of claims 1 - 5 or the branched PBAT resin according to any one of claims 6 - 8; Preferably, the preparation process includes: subjecting the branched PBAT resin to high-pressure impregnation with a supercritical gas, and then releasing the pressure; More preferably, the supercritical gas is supercritical carbon dioxide; More preferably, the operating pressure of the high-pressure impregnation is 15 MPa - 25 MPa, the temperature is 100 °C - 120 °C, and the impregnation time is 2 h - 4 h; More preferably, the pressure release rate is 5 MPa / s - 10 MPa / s.

10. A foam material, characterized in that, Prepared by using the preparation method according to claim 9; Preferably, the foaming ratio of the foam material is 20 - 25 times, the falling ball rebound rate ≥ 75%, and the degradation rate in 180 days > 90%.